How Fintech Peer to Peer Lending Affected MSMEs Financial Access: Case Study Amartha - Indah Permata Suryani; Atika Gando Suri; Zahra Shafira (InFestasi, 2023)
The recent emergence of financial technology (FinTech) is believed to be able to solve SME problems related to access to capital sources. One of the popular fintech business models is the online lending platform (Peer to Peer Lending) which is growing rapidly in Indonesia. This research will focus on one of the Peer to Peer lenders registered in Indonesia which has helped MSMEs in rural areas, namely PT Amartha Mikro Fintek (amartha.com). This study will reveal how P2P lending empowers MSMEs to support their business. This research will use descriptive qualitative with a case study approach. The research results show that P2P lending is an integral part of the Indonesian financial system and increases MSME inclusion. PT Amartha Mikro Fintek's micro loan model expands access. However, long-term sustainability depends on wise regulation and governance to ensure consumer protection as well as innovation.